Seismic behavior of liquid storage tanks with 2D and 3D base isolation systems - Kilic, Samet; Akbaş, Bülent; Shen, Jay; Paolacci, Fabrizio (Techno-Press, 2022)
In past major earthquakes (1994 Northridge, 1995 Kobe, Chi-Chi 1999, Kocaeli 1999), significant damages occurred in the liquid storage tanks. The basic failure patterns were observed to be the buckling of the tank wall and uplift of the anchorage system. The damages in the industrial facilities and nuclear power plants have caused the spread of toxic substances to the environment and significant fires. Seismic isolation can be used in liquid storage tanks to decouple the structure and decrease the structural demand in the superstructure in case of ground shaking. Previous studies on the use of seismic isolation systems on liquid storage tanks show that an isolation system reduces the impulsive response but might slightly increase the convective one. There is still a lack of understanding of the seismic response of seismically isolated liquid storage tanks considering the fluid-structure interaction. In this study, one broad tank, one medium tank, and one slender tank are selected and designed. Two-and three-dimensional elastomeric bearings are used as seismic isolation systems. The seismic performance of the tanks is then investigated through nonlinear dynamic time-history analyses. The effectiveness of each seismic isolation system on tanks' performance was investigated. Isolator tension forces, modal analysis results, hydrodynamic stresses, strains, sloshing heights and base shear forces of the tanks are compared. The results show that the total base shear is lower in 3D -isolators compared to 2D-isolators. Even though the tank wall stresses, and strains are slightly higher in 3D-isolators, they are more efficient to prevent the tension problem.
Keywords: 3D isolators; base isolation; tank seismic design